Bulgarian Translations of the Qurʾān (1900–2020): Missionary Agenda, Communist Ideology, and Canonical Impulse - Pavel Pavlovitch (Zeszyty Cyrylo-Metodiańskie)
The present paper aims to analyse the historical and political contexts in which the Bulgarian translations of Qurʾān were created and disseminated. The history of Bulgarian translations of Qurʾān may be divided into three periods: 1900–1944, 1944–1989 and the 1990s onward. The first period is dominated by two Protestant translations from English motivated by a missionary incentive. In the second period, translations of Qurʾān were controlled by the Communist state and thus suppressed or intended to justify persecutions against Bulgarian Muslims. The third period saw the publication of multiple Bulgarian translations of the Qurʾān as well as the first rendition from Arabic. All stages are carefully and critically examined to demonstrate the relevant socio-political influence on the Qurʾān’s presence in Bulgaria. The logical progression of approaches taken by subsequent translations is also shown. The paper concludes with a systematic summary of the status of the Qurʾān in Bulgaria, thereby suggesting possible directions for future researchers and translators.